When minority labor migrants meet the welfare state - Bernt Bratsberg; Oddbjørn Raaum; Knut Røed (Institute for the Study of Labor (IZA), 2007)
We find that the lifecycle employment profiles of nonwestern male labor migrants who came to Norway in the early 1970s diverge significantly from those of native comparison persons. During the first years after arrival almost all of the immigrants worked and their employment rate exceeded that of natives. But, about ten years upon arrival, immigrant employment started a sharp and steady decline. By 2000, the immigrant employment rate was 50 percent, compared to 87 percent for the native comparison group. To some extent, the decline in immigrant employment can be explained by immigrants being overrepresented in jobs associated with short employment careers. But we also identify considerable disincentives embedded in the social security system that contribute to poor lifecycle employment performance of immigrants with many dependent family members. Finally, we uncover evidence that labor immigrants are particularly vulnerable to the state of the economy and face a high probability of permanent exit from employment during economic downturns.
Keywords: 330; Internationale Arbeitsmobilität; Migranten; Erwerbsverlauf; Arbeitslosigkeit; Ethnische Gruppe; Norwegen